The Pedagogy of “Fear of Hell”: Analyzing Symbolic Violence in Primary Education - Putri, Rina Oktafia; Fatah, Ahmad (IJTIMAIYA: Journal of Social Science and Teaching, 2026)
This research aims to analyze the pedagogy of "fear of hell" as a form of language-based symbolic violence and to investigate how this covert domination affects primary school students. Rooted in Pierre Bourdieu’s sociological framework, this study examines the mechanisms through which school authorities utilize specific religious discourses, labels, and language to force young learners into compliance and submission without physical coercion. Using a qualitative field research method, data were gathered through observation, interviews, and documentation. The findings reveal that the deployment of "fear of hell" narratives functions as an instructional approach driven by theological discipline and extrinsic motivation, establishing an asymmetric power dynamic between teachers and students. Through vulgar depictions of afterlife punishments, teachers establish a high bargaining position of symbolic authority to shape student compliance. While this method is sociologically effective in creating instant discipline and rapid compliance, the research highlights significant negative psychological side effects on students, including trauma, pseudo-compliance, anxiety, and the inhibition of critical thinking and creativity. Ultimately, this study demonstrates how the education system can inadvertently become a site for cultural reproduction that normalizes symbolic violence through internalized fear.